Clinical Effects of Radiofrequency Coblation for Adult Laryngopharyngeal Vascular Lesions. (10th August 2020) - Jia, Junxiao; Zhang, Junbo; Xiao, Shuifang
Abstract : Objective: To explore the feasibility and efficacy of transoral radiofrequency coblation surgery (TRS) in the treatment of adult laryngopharyngeal vascular lesion (LVL). Methods: A total of 15 patients with LVL were retrospectively studied, including 11 capillary lesions and five cavernous lesions (there was one case with two separate lesions). All of the lesions were treated with TRS alone (capillary lesion) or with a combination of TRS and sclerotherapy (cavernous lesion). The treatment efficacy was evaluated according to the modified Achauer criteria: grade 1, no change in size; grade 2, a decrease of < 50% in size; grade 3, a decrease of ≥ 50% but < 100%; and grade 4, the disappearance of the lesion with no recurrence for at least 6 months. Results: The surgical procedures were successfully completed in all patients. According to the modified Achauer criteria, the treatment outcomes were grade 4 for 10 capillary lesions and one cavernous lesion; grade 3 for one capillary lesion and one cavernous lesion; grade 2 for one cavernous lesion; and grade 1 for two cavernous lesions, respectively. No complications related to the surgery, including bleeding, dysphagia, and infections, occurred after treatment. Conclusion: The TRS is an effective treatment option for LVL, especially for patients with laryngopharyngeal capillary lesions. Level of Evidence: 4 Laryngoscope, 131:566–570, 2021